2011
DOI: 10.12659/msm.881697
|View full text |Cite
|
Sign up to set email alerts
|

Access to biologic treatment for rheumatoid arthritis in Central and Eastern European (CEE) countries

Abstract: SummaryBackgroundThe aim of this study was to assess and compare patients’ access to biologic anti-RA drugs in selected Central and Eastern European (CEE) countries and to analyze the determinants of differences between countries.Material/MethodsThis is a multi-country survey study, based on a combination of desk research and direct contact with national RA stakeholders. Data was collected using a pre-defined questionnaire. Affordability was measured using an affordability index, calculated comparing the index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 8 publications
1
52
0
6
Order By: Relevance
“…In many countries reimbursement of biological treatment and monitoring during treatment is based on DAS28 scores [23]. Patients should not be labeled as non responders to biological therapy only based on the DAS28 score, but also based on US examination if available.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries reimbursement of biological treatment and monitoring during treatment is based on DAS28 scores [23]. Patients should not be labeled as non responders to biological therapy only based on the DAS28 score, but also based on US examination if available.…”
Section: Discussionmentioning
confidence: 99%
“…Population biological utilization rates measure consistently the overall access to these drugs, but do not provide insight into access levels and potential inequities between therapeutic areas or indications. Several authors report treatment rates of diagnosed patients (Kobelt -Kasteng 2009;Orlewska et al 2011;Péntek et al 2014;Poór 2015). It is important to note that methodological differences and different time-points of epidemiological studies resulted in wide variance of disease prevalence estimates (Kiss et al 2005;Hanova et al 2006;Kobelt and Kasteng 2009;EUMUSC 2011).…”
Section: Costs Of Biological Drugs Per Patientmentioning
confidence: 99%
“…Also, reports on the number of patients taking biologicals may rely on estimates from a mixture of sources. (Kobelt -Kasteng 2009;Orlewska et al 2011;Poór 2015) Although published studies provide valuable cross-sectional comparison of biological treatment rates in different time-points, there is insufficient research on the evolution of the diagnosis and biological treatment rates over time. In order to measure the effect of biosimilars on patient-access accurately, a consistent methodology is needed across time.…”
Section: Costs Of Biological Drugs Per Patientmentioning
confidence: 99%
“…It has been shown that initiation of DMARD treatment immediately after disease onset is associated with a better outcome compared with later usage. [14] Synthetic DMARDs are known to improve symptoms, articular findings, and physical function while also slowing down radiological progression. [15][16][17] Thus, the initial treatment approach should include synthetic DMARDs due to the high cost of biological DMARDs, which are also known to be effective in the early stage of the disease.…”
Section: General Recommendationsmentioning
confidence: 99%